Ionized-cluster beam deposition and epitaxy - Takagi, Toshinori (Noyes Publications, 1988)
The technique of ionized-cluster beam (ICB) deposition, the fundamentals of ICB technology, and technical applications of thin films produced by ICB deposition are presented for those interested or working in the field. ICB processes are characterized, and equipment is available. The films deposited are often superior to those deposited by either evaporation or sputtering, and the range of control of the process exceeds other techniques by a great margin.
Keywords: Epitaxy.; Thin film devices -- Design and construction.; elektronické knihy; electronic books